2015
DOI: 10.4236/ojra.2015.52009
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Neuropsychiatric Syndromes of Systemic Lupus Erythematosus

Abstract: The pathogenesis of neuropsychiatric syndromes of systemic lupus erythematosus (NPSLE) is multifactorial and can involve various inflammatory cytokines, autoantibodies such as anti-neuronal antibodies, anti-ribosomal P antibodies, anti-NR2 glutamate receptor binding antibodies, anti-Sm antibodies, anti-U1-RNP antibodies and anti-phospholipid antibodies, and immune complexes (IC). Disruption of the blood-brain barrier (BBB) is integral to the neuropathology of SLE.Recently the possibility has been reported that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Furthermore, our study revealed a significant positive correlation between CSF anti-P titres and serum anti-P titres in 52 patients with SLE, suggesting that the presence of CSF anti-P might be influenced by serum anti-P. Our group previously reported that anti-P binds to endothelial cells and stimulates them. 30,31 Thus, circulating anti-P might bind to endothelial cells in the BBB, leading to vascular inflammation and damage to the BBB, thereby resulting in the penetration of anti-P into the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study revealed a significant positive correlation between CSF anti-P titres and serum anti-P titres in 52 patients with SLE, suggesting that the presence of CSF anti-P might be influenced by serum anti-P. Our group previously reported that anti-P binds to endothelial cells and stimulates them. 30,31 Thus, circulating anti-P might bind to endothelial cells in the BBB, leading to vascular inflammation and damage to the BBB, thereby resulting in the penetration of anti-P into the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The major inflammatory mediators released from immune cells act on sensory neurons inducing peripheral sensitization and hyperalgesic phenomena; moreover, after an injury, this natural inflammatory response could facilitate the pathogenetic activity of antineural autoantibodies, in addition to ischemic vascular mechanism by vasa nervorum vascularitis or by microthrombi linked to antiphospholipid antibodies. The other legitimate mechanisms are: immunologic effect by a direct antibodies aggression, entraining destruction of the peripheral nerve component [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…All these findings, and others published more recently in NPSLE patients, suggest that NMDAR Abs are directly implicated in neurodegeneration [34,105]. Recently, authors proposed that anti-NR2 Abs and NF K B activation may generate NPSLE pathogenesis [28]. An observation that may be highly relevant concerning reversibility of symptoms is that depending on their concentration, NMDAR Abs may either induce neuronal perturbation by transitory increment of excitatory postsynaptic potentials, or provoke neuronal death [101,106].…”
Section: Immune Cells Autoabs and Neuroimmunologymentioning
confidence: 91%